(untitled) (Fiep Bulletin - online, 2016)
Leisure is a social right of all citizens guaranteed by the Constitution, by the Statute of Children and Adolescents , by the Elderly Statute and the National Policy for the Integration of People with Disabilities. In this study, from a qualitative perspective, we sought to identify, through observations and semi-structured interviews, the importance of recreational public spaces have so as to improve life quality, relating Physical Education to this field of activity as well as its importance in the educational processes for and at leisure when urban space, environment, autonomy and quality of life are considered. It was found that there is lack of public policies to effectively and efficiently address the community members’ wishes and recreational needs as there is no participation of the residents in the development and construction of projects. The importance of leisure facilities as an approximation element between people and an element of culture production, of identity with their fellows, of identifying leisure as a social right acquired with quality of life, and socialization as a motivational element is evident. Finally, pleasure is discussed as a social right and a condition for good quality of life and civic formation with dignity, ethics and equality.